Experience Bharatnatyam through the Lens of Connected Devices - Vandana Bharadwaj, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The COVID-19 pandemic has compelled the performing arts community to explore virtual platforms as a means of continuing their artistic practices. Bharatanatyam, a classical Indian dance form, has also witnessed a shift towards virtual training and performance. The purpose of this abstract is to share my experience in training and performing Bharatanatyam on a virtual platform and discuss the benefits and drawbacks. Alongside I have made an effort to list down few strategies to mitigate the technological drawback to safeguard Bharatnatyam's authenticity and cultural heritage.
Keywords: Augmented Reality (AR); Virtual Reality (VR); High Definition (HD); Ultra High Definition (UHD); $4096×4096$ Resolution (4K); Three Dimension (3D)